MEMS: Enabled Drug Delivery Systems. Issue 7 (20th February 2015) - Cobo, Angelica; Sheybani, Roya; Meng, Ellis
<x xml:space="preserve">Abstract</x> Drug delivery systems play a crucial role in the treatment and management of medical conditions. Microelectromechanical systems (MEMS) technologies have allowed the development of advanced miniaturized devices for medical and biological applications. This Review presents the use of MEMS technologies to produce drug delivery devices detailing the delivery mechanisms, device formats employed, and various biomedical applications. The integration of dosing control systems, examples of commercially available microtechnology‐enabled drug delivery devices, remaining challenges, and future outlook are also discussed.